PEMBUATAN GAME FIRST PERSON SHOOTER “FIND ME! SHOOT ME!” DENGAN FITUR SPLIT SCREEN - Dominic Oscar; Jeanny Pragantha; Darius Andana Haris (Computatio : Journal of Computer Science and Information Systems, 2018)
Game “Find Me! Shoot Me!” is a game that has First Person Shooter Genre with split screen feature in one screen and invisible character that is visual of the character is not visible. This game was created with the aim of providing a First Person Shooter game experience that is different than usual. This game has a 3D display and played using a windows based computer or laptop and using joystick controller for the control tool.This game was created using Unity with C# as a programming language. Player are assigned to search and kill other players. The game will end if one the player has reached a predetermined point. This multiplayer game feature is played at least two players and maximum of four players.